KOMUNIKASI KRISIS DI TENGAH PANDEMI COVID 19 GBI PONDOK TOBA DELI SERDANG - Dewi Sartika Butarbutar; Irene Silviani (JURNAL PROINTEGRITA, 2021)
Covid – 19 pandemic has changed the structure of human life, especially in the field of communication, which resulted in a communication crisis in the middle of the GBI Pondok Toba community. This study aims at analyzing crisis communication in the middle of Covid – 19 pandemic of GBI Pondok Toba Deli Serdang. This research uses descriptive qualitative research methods. As a result of this pandemic has resulted in a communication crisis ranging from a lack of understanding of the Covid – 19 pandemic, ignoring government recommendations to use masks and other protective devices, the emergence of several conflicts in the congregation's household due to financial factors and other individual problems, reduced family feeling because of the thought to keep a distance even though it can be done through the media and the lack of attention of church leaders for disadvantaged congregants, widows and the elderly. Church leaders must change the way they communicate to provide solutions to the communication of the crisis that occurred.